185 Treatment of Intravaginal Ejaculation Disorder Using Ejaculation Aids: A Multicenter Prospective Clinical Trial. (1st May 2022) - Fukuhara, S.; Takezawa, K.; Kiuchi, H.; Nonomura, N.; Iwasa, A.; Kobayashi, K.; Shirai, M.; Tsujimura, A.
ABSTRACT: Introduction: Ejaculation disorders, the second most common sexual dysfunction, are often difficult to treat because of the lack of highly effective treatments. The A10 cyclone SA +PLUS (Fig. 1 ) is a motorized ejaculation aid with adjustable movement and intensity of stimulation. The A10 cyclone SA +PLUS. We hypothesized that the A10 cyclone SA +PLUS would be effective in the treatment of ejaculation disorders. Objective: To evaluate the efficacy of the A10 cyclone SA +PLUS ejaculation aid in the treatment of intravaginal ejaculation disorder. Methods: Between August 2020 and May 2021, men from 20 to 60 years of age who visited our hospital with complaints of vaginal ejaculation disorder were included. Patients were treated with masturbation using the A10 cyclone SA +PLUS 1–3 times a week for 8 weeks. A questionnaire was used to assess the ability to achieve vaginal ejaculation before and after the intervention. Sexual function was also assessed using questionnaires such as IIEF, EHS, MSHQ-EjD, CPSIQ-12, and NRS (Numerical Rating Scale) before and after the intervention. The procedures were approved by the Regional Ethics Committee (approval number: 2020-007). All patients provided written informed consent. Results: Eight patients were included in this study. The median age was 35 years. Three of Eight (38%) patients achieved vaginal ejaculation. Significant improvement was found in IIEF and EH. Conclusions: Ejaculation aids may be an effective treatment for vaginal ejaculation disorder, for which any drug has not been effective. We plan to conduct further studies to increase the number of patients. Disclosure: Work supported by industry: no.